Blood pressure and its associated factors: a comparative study among rural and urban adolescents in Bangladesh - Taleb, Mohammad A.; Ahmed, MSA M.; Sharmin, Kazi N.; Islam, D. (International Journal of Research in Medical Sciences, 2016)
Background: Hypertension in adolescents may lead to irreversible damages in vital organs, such as heart, brain, kidney and may cause death if treatments are not given despite early diagnosis. The aim of this study is to identify the status of blood pressure and its associated factors among adolescents. Methods: It was a cross-sectional study. 810 adolescents of 8 schools and colleges in Chittagong district were collected by stratified cluster sampling technique. Ages of the respondents were 14 to 19. Status of Blood pressure and its associated factors in urban and rural area were the main outcome of interest. Results: The study found the significant difference in physical activities and overweight statistics between urban and rural adolescents (P<0.001). Obesity was found only in the urban area that was 1.2%. The mean systolic blood pressure (114.53 mmHg, 110.61 mmHg) and mean diastolic blood pressure (69.87 mmHg, 68.58 mmHg) of boys and girls in urban respondents were more than rural (109.79 mmHg, 68.97 mmHg and 105.02 mmHg, 67.941 mmHg respectively) and was statistically significant (P<0.001). The mean SBP and DBP were 126 mmHg and 79 mmHg respectively among obese. In the study prevalence of hypertension was 1.5% in urban adolescents and 0.2% in rural adolescents. Consumption of fast food, living area, physical activity, paternal hypertension and BMI were found significantly associated (p<0.05) with hypertension among urban adolescents. Conclusions: The results suggest that hypertension and pre-hypertension is an important public health problem among adolescents in urban than rural. The main associated factors are fast food consumption, living area, physical activity, paternal hypertension and BMI.